Parentocracy : the new meritocracy in the face of widening social inequality - Tay, Joash (2015)
The Singapore education system strictly observes meritocracy. It rewards students based on individual academic performance and effort. However, meritocracy places students with fundamentally different background on seemingly equal footing, allowing parents to leverage on the meritocratic education system by providing an unfair advantage for their children. This gives rise to the notion of “parentocracy”, “where a child’s education is increasingly dependent upon the wealth and wishes of parents, rather than the ability and efforts of pupils” (Brown 1990: 66). With an increase in parental intervention, this results in unequal advantages bestowed on students by virtue of the differing social class of their parents; the accumulation of which tends to reproduce and widen the social inequality in Singapore.